Snow loads : guide to the snow load provisions of ASCE 7-16 - O'Rourke, Michael J. (American Society of Civil Engineers, 2017)
Michael O'Rourke provides an detailed and authoritative interpretation of the snow load provisions of Standard ASCE/SEI 7-16, accompanied by 35 practical design examples.